Preface: THE LANGUAGE OF PANDEMICS - Franca Daniele (European Scientific Journal, ESJ, 2020)
ESJ Special Edition10 years European Scientific Journal, ESJTopic: The language of PandemicsGuest Editor: Franca Daniele, MDDepartment of Medical, Oral and Biotechnological Sciences “G. d’Annunzio” University – Chieti-Pescara, Italy